Universities as change agents in resource-poor local settings: An empirically grounded typology of engagement models - Petersen, Il-haam; Kruss, Glenda (Technological Forecasting & Social Change, 2021)
University-community engagement is emerging as an important channel for social innovation, requiring universities to act as change agents in their local settings. The role of change agent presents new challenges for universities as it requires going beyond institutional borders to collaborate with non-traditional partners such as informal enterprises, and to stimulate and support innovation that may be seen as relevant to a given local setting only. Universities are thus grappling with finding suitable mechanisms and models for engaging in institutional contexts that are vastly different from traditional formal university- and firm-based settings. Based on empirically rich case study research in a South African township, the paper presents new conceptual insights on how universities can catalyse social change in resource-poor local settings through strategically selecting mechanisms and models of engagement that align with locally-embedded institutions, practices and needs. Four types of engagement models are identified, each relate to different models of entrepreneurship and innovation and thus different modes of learning. The typology distinguishes between dominant, traditional knowledge transfer models, and emergent, socially responsive models that show greater promise for promoting collective agency and effecting systemic social change. The typology can be used to assess current practice and inform future strategies.
Keywords: Afrique; Réservé UdeM; Rôle des universités